PP.27.22: SERUM URIC ACID LEVELS ARE ASSOCIATED WITH CAROTID PLAQUE ECHOLUCENCY IN PATIENTS WITH CAROTID ATHEROSCLEROTIC DISEASE. (June 2015) - Camerota, A.; Mastroiacovo, D.; De Ciantis, P.; Cola, S.; D'Onofrio, P.P.; Grassi, D.; Pinelli, M.; Necozione, S.; Ferri, C.; Desideri, G.
Abstract : Objective: We studied 91 patients aged 65 years or more (72.5 ± 5.7 years) from our angiology unit. At enrolment, patients underwent ultrasonography of the neck vessels using a 7–8 MHz linear probe; images were stored on magneto-optical disk and subsequently used to calculate the grey scale median (GSM) using Adobe Photoshop 5.0. The calculation of the GSM was performed by researchers blinded to the clinical characteristics of patients. Design and method: We studied 91 patients aged 65 years or more (72.5 ± 5.7 years) from our angiology unit. At enrolment, patients underwent ultrasonography of the neck vessels using a 7–8 MHz linear probe; images were stored on magneto-optical disk and subsequently used to calculate the grey scale median (GSM) using Adobe Photoshop 5.0. The calculation of the GSM was performed by researchers blinded to the clinical characteristics of patients. Results: Circulating levels of SUA showed a trend toward a correlation with plaque echolucency in the study population considered as a whole (Table). Due to some evidence suggesting a "J curve" relationship between SUA levels and atherosclerotic events we also evaluated the relationship between SUA levels and plaque echolucency in 3 subgroups of patients distinguished according to SUA thresholds higher than 3 o 4 or 5 mg/dL, respectively. We found that the strength of the relationship between SUA concentration and plaque echolucency increased through the different thresholds (Table). Figure. No caption available. Conclusions: Our study points to an association between increased circulating levels of uric acid and plaque echolucency. These data suggest that serum uric could play an influential role on the atherosclerotic plaque morphology and stability.